Design and Development of Ball Bearing for Inclined Loads - Ahmad Rafie bin Mohmad Tahir, Ahmad Rafie (Universiti Teknologi Petronas, 2010)
A journal bearing is a mechanical component that is used to allow constrained relative motion between two or more parts, typically rotation or linear movement. Bearings may be classified generally according to the motions they allow and according to their principle of operation as well as by the directions of applied loads they can handle. Typically, ball bearings are designed to accommodate either axial or radial load. They are not capable of handling both the load simultaneously. A slewing bearing is a special type of bearing that can accommodate axial as well as radial load simultaneously. At present, their application including heavy cranes, large wind turbine, excavation machinery and all kinds of harbor and shipyard cranes. For smaller loads, there is no slewing bearing that has been design due to the complexity of its manufacturing. This research study could be looking into the design aspects of slewing bearing and its manufacturing technology for small loads applications. This paper contains the fundamental understanding of slewing bearing design and its calculation theories. Also, this paper included the calculation results and also the detail design of the slewing bearing.